Role of Contrast-Enhanced Ultrasound (CEUS) in Native Kidney Pathology: Limits and Fields of Action - Granata, Antonio; Campo, Irene; Lentini, Paolo; Pesce, Francesco; Gesualdo, Loreto; Basile, Antonio; Cantisani, Vito; Zeiler, Matthias; Bertolotto, Michele (Diagnostics (Basel), 2021)
Gray scale ultrasound has an important diagnostic role in native kidney disease. Low cost, absence of ionizing radiation and nephrotoxicity, short performance time, and repeatability even at the bedside, are the major advantages of this technique. The introduction of contrast enhancement ultrasound (CEUS) in daily clinical practice has significantly reduced the use of contrast enhancement computed tomography (CECT) and contrast enhancement magnetic resonance (CEMR), especially in patients with renal disease. Although there are many situations in which CECT and CEMRI are primarily indicated, their use may be limited by the administration of the contrast medium, which may involve a risk of renal function impairment, especially in the elderly, and in patients with acute kidney injury (AKI) and moderate to severe chronic kidney disease (CKD). In these cases, CEUS can be a valid diagnostic choice. To date, numerous publications have highlighted the role of CEUS in the study of parenchymal micro-vascularization and renal pathology by full integration with second level imaging methods (CECT and CEMRI) both in patients with normal renal function and with diseased kidneys. The aim of this review is to offer an updated overview of the limitations and potential applications of CEUS in native kidney disease.